The Feasibility of E-Learning Media on Anecdote Text Material for X Grade Students of Senior High School Harapan 3 Delitua, Indonesia - Zulfikar Alamsyah; Abdurrahman Adisaputera; Isda Pramuniati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The feasibility of anecdote text e-learning based learning media is based on the validation test of material experts and design experts. After being validated, the research products can be tested on individual students, small groups and limited groups. The following will be explained the feasibility test of e-learning based text and text learning media. Research methods in this research plan include: location and time of study, population and sample of research, research design, operational definition, research procedures, types of data, techniques and data collection instruments. The conclusion is that the use of e-learning based anecdote text learning media is more effective than non-e-learning based learning, this can be seen from the average results of the pretest and posttest and the achievement of the indicator value of students in using e-learning learning media.